Variation of Finger Activation Patterns Post-stroke Through Non-invasive Nerve Stimulation - Shin, Henry; Zheng, Yang; Hu, Xiaogang (Frontiers in Neurology, 2018)
Purpose: A transcutaneous proximal nerve stimulation technique utilizing an electrode grid along the nerve bundles has previously shown flexible activation of multiple fingers. This case study aimed to further demonstrate the ability of this novel stimulation technique to induce various finger grasp patterns in a stroke survivor. Methods: An individual with chronic hemiplegia and severe hand impairment was recruited. Electrical stimulation was delivered to different pairs of an electrode grid along the ulnar and median nerves to selectively activate different finger flexor muscles, with an automated electrode switching method. The resultant individual isometric flexion forces and forearm flexor high-density electromyography (HDEMG) were acquired to evaluate the finger activation patterns. A medium and low level of overall activation were chosen to gauge the available finger patterns for both the contralateral and paretic hands. All the flexion forces were then clustered to categorize the different types of grasp patterns. Results: Both the contralateral and paretic sides demonstrated various force clusters including single and multi-finger activation patterns. The contralateral hand showed finger activation patterns mainly centered on median nerve activation of the index, middle, and ring fingers. The paretic hand exhibited fewer total activation patterns, but still showed activation of all four fingers in some combination. Conclusion: Our results show that electrical stimulation at multiple positions along the proximal nerve bundles can elicit a select variety of finger activation patterns even in a stroke survivor with minimal hand function. This system could be further implemented for better rehabilitative training to help induce functional grasp patterns or to help regain muscle mass.